Six Autoimmune Disorders Are Associated With Increased Incidence of Gastric Cancer: A Systematic Review and Meta-Analysis of Half a Million Patients - Zádori, Noémi; Szakó, Lajos; Váncsa, Szilárd; Vörhendi, Nóra; Oštarijaš, Eduard; Kiss, Szabolcs; Frim, Levente; Hegyi, Péter; Czimmer, József (Frontiers in Immunology, 2021)
Background: Gastric cancer is one of the most common cancer worldwide, with a high mortality rate. The potential aetiological role of autoimmune (AI) disorders have been described in gastric cancer; however, the literature is controversial. This study aims to provide a comprehensive summary of the association between autoimmune disorders and the incidence of gastric cancer. Methods: This study was registered on PROSPERO under registration number CRD42021262875. The systematic literature search was conducted in four scientific databases up to 17th May 2021. Studies that reported standardized incidence rate (SIR) of gastric cancer in autoimmune disorders were eligible. We calculated pooled SIRs with 95% confidence intervals (CIs) in this meta-analysis. Results: We included 43 articles describing 36 AI disorders with data of 499,427 patients from four continents in our systematic review and meta-analysis. Significantly increased incidence of gastric cancer was observed in dermatomyositis (SIR= 3.71; CI: 2.04, 6.75), pernicious anemia (SIR= 3.28; CI: 2.71, 3.96), inflammatory myopathies (SIR= 2.68; CI:1.40; 5.12), systemic lupus erythematosus (SIR= 1.48; CI: 1.09, 2.01), diabetes mellitus type I (SIR= 1.29; CI:1.14, 1,47), and Graves’ disease (SIR= 1.28; CI: 1.16, 1.41). No significant associations could be found regarding other AI disorders. Conclusions: Pernicious anaemia, Graves' disease, dermatomyositis, diabetes mellitus type I, inflammatory myopathies, and systemic lupus erythematosus are associated with higher incidence rates of gastric cancer. Therefore, close gastroenterological follow up or routinely performed gastroscopy and application of other diagnostic measures may be cost-effective and clinically helpful for patients diagnosed with these autoimmune diseases.